Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1152/japplphysiol.00125.2017
|View full text |Cite
|
Sign up to set email alerts
|

Aging is associated with increased propensity for central apnea during NREM sleep

Abstract: The reason for increased sleep-disordered breathing with predominance of central apneas in the elderly is unknown. We hypothesized that the propensity to central apneas is increased in older adults, manifested by a reduced carbon-dioxide (CO) reserve in older compared with young adults during non-rapid eye movement sleep. Ten elderly and 15 young healthy adults underwent multiple brief trials of nasal noninvasive positive pressure ventilation during stable NREM sleep. Cessation of mechanical ventilation (MV) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 57 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…The arousal indexes were also generally higher at 10-year follow-up than baseline in all OSA subtypes, which was consistent with previous findings of decreasing arousal threshold with increasing age. 42 Similarly, the changes in ventilatory control during sleep with aging have not been fully elucidated. As there is an increasing prevalence of SDB and central apneas in the elderly, it is postulated that the stability in ventilatory control decreases with aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arousal indexes were also generally higher at 10-year follow-up than baseline in all OSA subtypes, which was consistent with previous findings of decreasing arousal threshold with increasing age. 42 Similarly, the changes in ventilatory control during sleep with aging have not been fully elucidated. As there is an increasing prevalence of SDB and central apneas in the elderly, it is postulated that the stability in ventilatory control decreases with aging.…”
Section: Discussionmentioning
confidence: 99%
“…The arousal indexes were also generally higher at 10-year follow-up than baseline in all OSA subtypes, which was consistent with previous findings of decreasing arousal threshold with increasing age. 42 Similarly, the changes in ventilatory control during sleep with aging have not been However, studies have demonstrated contrasting results in this aspect that some reported an increase in loop gain in the elderly 42 while others did not. 43 Further studies are needed to evaluate how the ontogenetic variations in the endotypes, including airway collapsibility, arousal threshold, and ventilatory control, influence the patterns of occurrence of disordered breathing in different sleep stages across age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly central apneas are common in the elderly due to increased breathing instability during non-REM sleep, as suggested by a lower carbon dioxide reserve and a higher controller gain (6). Despite the pharyngeal muscle function and the size of the airway lumen being reduced in elderly people, an increase in arousal frequency due to aging causes hyperventilation and hypocapnia, which promote respiratory instability (7). These two studies of Chowduri et al were both contrary to our study while in our study oxygen saturation values of the elderly were not significantly different from the younger OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased controller gain may explain increased propensity to central apnea in men vs premenopausal women, 14 and in older adults compared with young and middle-aged adults. 15 Likewise, patients with OSA also exhibit a higher propensity to induced central apnea, and higher loop gain, compared with healthy matched adults. 13 Interestingly, PAP therapy for 4 weeks is associated with decreased controller gain and widening of the CO 2 reserve.…”
Section: Determinants Of Breathing Instability During Sleep: Lessons From Physiologic Studiesmentioning
confidence: 99%